Joint imaging and communication using sparse antenna arrays - Abusanad, Nusaibah A.; Ayasrah, Mus'ab; Arslan, Hüseyin (My University, 2024)
This paper expands sensing capabilities by providing a Joint Imaging and Communication (JIC) system, leveraging millimeter-wave (mm-Wave) technology and sparse antenna array. To address the challenges associated with the high cost and power consumption of dense antenna arrays, we use a sparse antenna array (SAA) to avoid such a problem at the expense of image resolution. The enhancement of acquired image resolution is achieved through the incorporation of multiple low-resolution image components corresponding to distinct transmission-reception combinations. In order to achieve a high level of fairness between communication and imaging performance we formulate a non-convex optimization problem, and then propose an algorithm for finding an approximate solution in a fully digital beamforming case. Numerical results on achievable capacity and image resolution are presented to validate the proposed approach and provide insights into system performance.
Keywords: Active Sensing; Digital Beamforming; Joint Imaging and Communication; Joint Sensing and Communication; Sparse Antenna Array